ANALISIS PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PTS X DI JAKARTA - Soerjanto (LPPM Universitas Asa Indonesia, 2019)
Purpose- The aim of this study is to Analyze Effect Of Leadership Style And Motivation On Emplyee’s Performance. Design/methology/approach- The primary data and secondary ones were collected by a set of questionair. Analysis method were descriptive and multiple regression for quantitave method. Findings- The findings were found that there are positive influence of leadership style and motivation on employees’s performance partially and simultaneously. Keywords : Leadership Style, Motivation, Emplyee’s Performance.